2009
DOI: 10.1371/currents.rrn1126
|View full text |Cite
|
Sign up to set email alerts
|

The early diversification of influenza A/H1N1pdm

Abstract: Background Since its initial detection in April 2009, the A/H1N1pdm influenza virus has spread rapidly in humans, with over 5,700 human deaths. However, little is known about the evolutionary dynamics of H1N1pdm and its geographic and temporal diversification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
187
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(207 citation statements)
references
References 18 publications
18
187
1
1
Order By: Relevance
“…They have been previously reported by Ledesma et al (10), who demonstrated that Spanish viruses carried D97N, S83P, S185T, and V321I mutations, which were also found in the viruses circulating in Poland. Remarkably, P83 and I321 points diagnosed only in the HA gene of 134312 virus were present in the vaccine A/H1 component, and the first pandemic A(H1N1)2009 isolates were all classified in one pattern group (15). the S185T mutation, which occurred in A/Poland/031925/2012 virus, was identical as in the previously identified Northern hemisphere pdm SIV and the SIVs widely spread in Spain (10).…”
Section: Discussionsupporting
confidence: 52%
“…They have been previously reported by Ledesma et al (10), who demonstrated that Spanish viruses carried D97N, S83P, S185T, and V321I mutations, which were also found in the viruses circulating in Poland. Remarkably, P83 and I321 points diagnosed only in the HA gene of 134312 virus were present in the vaccine A/H1 component, and the first pandemic A(H1N1)2009 isolates were all classified in one pattern group (15). the S185T mutation, which occurred in A/Poland/031925/2012 virus, was identical as in the previously identified Northern hemisphere pdm SIV and the SIVs widely spread in Spain (10).…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, the amino acid changes mapped in the NA (V106I and N248D) and the S203T (S220T) mapped in the HA indicated that the majority of isolates from the three countries seems to belong to clades 3, 6, and 7, which is in agreement with recent results. 13 The P83S (P100S) and I321V (I338V) were mapped in all isolates, and the S203T (S220T) was in 8 of 14 sequenced isolates. It is important to specify that, in a recent study conducted in Brazil, 22 the S220T mutation was identified in 78.6% of fatal pandemic influenza cases.…”
Section: Discussionmentioning
confidence: 98%
“…This study clearly indicates that the cosmopolitan clade VII viruses are continuously circulating in India. This molecular epidemiology information will facilitate better pandemic planning and response capacity for future epidemiological surveillance in Indian subcontinent and abroad [22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%